Projectile seating depth influence on a small arms cartridge performance - Piasta, Krzysztof; Michalski, Jakub; Fikus, Bartosz; Kupidura, Przemysław (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2024)
Abstract In the world of small-arms ammunition, precision reigns supreme. The most significant feature of ammunition for shooters is undoubtedly the repeatability from one shot to the next. This study explores the detailed assembly process of small arms cartridges, leveraging modern machinery and innovative designs employed by cartridge manufacturers. It emphasizes how these tools ensure the fundamental repeatability and precision necessary for the quality of each batch of rounds. Establishing standards for the highest possible quality requires assessing the impact of imprecise cartridge assembly on ballistic performance. Utilizing a free-flight ballistic tunnel, a high-speed camera, light- and target-screen systems, the authors analyzed the effects of varying projectile seating depths thus affecting cartridge overall lengths (COAL) and cartridge base to ogive distance (CBTO) on the initial velocity and bullets’ point of impact at 50 meters. The study was conducted for two types of projectiles, differing in their ogive profiles: secant and tangent ogive. The performance differences between these profiles provided valuable insights for future projectile designs, highlighting that low-drag projectiles are slightly more sensitive to the seating depth than tangent profile bullets, and the importance of it should be considered in mass, military production as well. It is a valuable resource for analyzing the trade-off between producing bullets with a low drag coefficient and ensuring high precision. The research enhances the understanding of internal and external ballistics but most importantly draws attention to the importance of the standards of assembly processes to ensure optimal performance and safety in the field. Streszczenie Zapewnienie powtarzalności między kolejnymi strzałami jest niewątpliwie najistotniejszą cechą nabojów dla każdego strzelca. Autorzy poddali analizie proces montażu nabojów do broni strzeleckiej, wykorzystujący nowoczesne maszyny i innowacyjne rozwiązania konstrukcyjne stosowane przez światowych producentów amunicji. Biorąc pod uwagę jakość wykonanej amunicji, te narzędzia są wykorzystywane do zapewnienia jak największej dokładności i powtarzalności, które są fundamentalne w kwestii kontroli jakości partii nabojów. W celu wypracowania odpowiedniego standardu zapewniającego wymaganą jakość amunicji, istotne jest oszacowanie wpływu nieprecyzyjnego montażu nabojów na ich charakterystyki balistyczne. Przeprowadzając badania w tunelu balistycznym z wykorzystaniem kamery szybkiej oraz bramek prędkościowych i współrzędnościowych, przeanalizowano wpływ zmiennej głębokości osadzenia pocisku, a więc również całkowitej długości nabojów (COAL) oraz odległości od dna łuski do części ostrołukowej (CBTO) na prędkość wylotową i punkt trafienia pocisków na odległości 50 metrów. Analizy przeprowadzono dla różnych typów pocisków, różniących się kształtem części ostrołukowej. Wpływ różnic w ich konstrukcji na charakterystyki balistyczne jest istotny pod względem przyszłościowych nabojów, ponieważ pociski o mniejszym współczynniku oporu czołowego – większym promieniu profilu części ostrołukowej, są wrażliwsze na głębokość osadzenia, niż pociski o profilu ostrołuku stycznym do części cylindrycznej, które charakteryzują się większym współczynnikiem oporu czołowego. Analizowane różnice okazują się istotne również w masowej produkcji amunicji wojskowej. Wyniki stanowią cenne źródło informacji w poszukiwaniu kompromisu między produkcją pocisków o niskim współczynniku oporu aerodynamicznego, a zapewnieniem wysokiej precyzji. Praca pogłębia zrozumienie balistyki wewnętrznej i zewnętrznej, ale przede wszystkim zwraca uwagę na znaczenie jakości procesu montażu amunicji w kwestii zapewnienia optymalnej skuteczności zastosowania i bezpieczeństwa na polu walki.